PERAN PENDIDIKAN NON FORMAL TAMAN PENDIDIKAN AL-QUR’AN AL- WAZIRIYAH DALAM PENINGKATAN PEMAHAMAN MATERI TENTANG THAHARAH PADA PESERTA DIDIK DI SEKOLAH DASAR - Gio Apriansyah; Fajri Ismail; Muhammad Win Afgani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Non-formal education is a systematic activity outside the school system that is useful for increasing knowledge or understanding of students in achieving their learning goals. Non-formal education itself has the following characteristics: short-term education, more flexible registration requirements, learning places outside the classroom or in the classroom, conditions that are not strict and not limited to certain students and curricula. One example of non-formal education that is well-known in Indonesian society today is the Al-Qur'an Education Park. This study uses a qualitative approach with descriptive methods. A qualitative approach is a research method used to examine natural object conditions, where the researcher is the key instrument. several methods, namely the method, interviews and implementation. In connection with this research, the source of data from this study consisted of persons consisting of administrators of the Al-Qur'an educational park, ustadz or educators, and students or students. This paper aims to describe and examine more deeply the non-formal education of Al-Qur'an and Taharah Education Parks for students in elementary schools.